2021
DOI: 10.3390/ijms22137156
|View full text |Cite
|
Sign up to set email alerts
|

Dysregulation of miRNA in Leukemia: Exploiting miRNA Expression Profiles as Biomarkers

Abstract: Micro RNAs (miRNAs) are a class of small non-coding RNAs that have a crucial role in cellular processes such as differentiation, proliferation, migration, and apoptosis. miRNAs may act as oncogenes or tumor suppressors; therefore, they prevent or promote tumorigenesis, and abnormal expression has been reported in many malignancies. The role of miRNA in leukemia pathogenesis is still emerging, but several studies have suggested using miRNA expression profiles as biomarkers for diagnosis, prognosis, and response… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 190 publications
(249 reference statements)
1
25
0
Order By: Relevance
“…Some of them such as BCR and NF-kB [ 47 , 48 ], Pi3K/AKT [ 33 , 49 ], WNT [ 50 ], NOTCH-1 [ 51 ], and IL-4/CD40L [ 38 ], are boosted after microenvironment interactions during disease progression [ 52 ]. Different works illustrate how miRNAs are often involved in the regulation of these pathways in leukemias in general [ 53 ] and in CLL in particular [ 54 ]. miRNAs can function both as oncogenes and tumor suppressors, depending on the target gene, and the mechanism can be related to the different cancer hallmarks [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Some of them such as BCR and NF-kB [ 47 , 48 ], Pi3K/AKT [ 33 , 49 ], WNT [ 50 ], NOTCH-1 [ 51 ], and IL-4/CD40L [ 38 ], are boosted after microenvironment interactions during disease progression [ 52 ]. Different works illustrate how miRNAs are often involved in the regulation of these pathways in leukemias in general [ 53 ] and in CLL in particular [ 54 ]. miRNAs can function both as oncogenes and tumor suppressors, depending on the target gene, and the mechanism can be related to the different cancer hallmarks [ 8 ].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, a plethora of plasma miRNA have been characterized as diagnostic, prognostic, and predictive markers in gastrointestinal, hematologic, lung, prostate, and testicular cancers (among many others). 110-113 As an example, Hansen et al have studied miRNA-126 in patients with metastatic colorectal cancer receiving chemotherapy and bevacizumab and have shown that patients with progressive disease tended to have increasing miRNA-126 levels through therapy compared with patients with stable disease or partial/complete responses. 114 Screens for miRNA recapitulating responses to therapy have also been conducted, such as a recent study by Benson et al in which the authors identified miRNA-148a as a surrogate for response in patients with recurrent platinum-resistant ovarian cancer receiving carboplatin and decitabine.…”
Section: Circulating Nucleic Acidsmentioning
confidence: 99%
“…At present, there are thousands of miRNA, which constitute the most abundant class of gene regulatory system in cells [26]. Most of the miRNA expressions are highly tissue-speci c and cell-speci c, so they can be used in disease diagnosis and treatment, which has become a new research focus [27,28,29,30]. The main function of miRNA is the post-transcriptional regulation of protein-coding genes, which binds to the target mRNA and inhibits its translation in a sequence-dependent manner [31,32,33].…”
Section: Syk Downregulation Reversed the Effects Of Mir-339-5p On Hbzy-1 Cellsmentioning
confidence: 99%